Intermolecular Nucleophilic Addition Reaction of a C-7 Anion from N-[Bis(dimethylamino)phosphoryl]indole to Electrophiles/Arynes: Synthesis of 7-Substituted Indoles - Sharma, Esha; Kaur, Manjot; Kaur, Babaldeep; Kaur, Amarjit; Singh, Paramjit; Singh, Kamal Nain (Synlett, 2021)
A novel approach to the C-7 substitution of N-[bis(dimethylamino)phosphoryl]indole by nucleophilic addition of the corresponding C-7 carbanion to electrophiles or arynes is described. The directing group can be easily removed, providing a simple route to the synthesis of 7-functionalized indoles.
Keywords: indoles; lithiation; arylation; substitution; directing groups